Interview with Kenyatta Gilbert and HyeRan Kim-Cragg, Senior Advisors for “Assessing Pedagogical Diversity, Equity, and Inclusion in the Academy of Homiletics” (Homiletic, 2025)
Interview with Kenyatta Gilbert and HyeRan Kim-Cragg, Senior Advisors for “Assessing Pedagogical Diversity, Equity, and Inclusion in the Academy of Homiletics”